Delmira Agustini, sexual seduction, and vampiric conquest - Jrade, Cathy Login (Major figures in Spanish and Latin American literature and the arts., 2012)
"Delmira Agustini (1886-1914) has been acclaimed as one of the foremost modernistas and the first major woman poet of twentieth-century Spanish America. Critics and the reading public alike were immediately taken by the originality and power of her verse, especially the aggressively sexualized perspective never before found in texts written by Spanish American women. Agustini sought, like the men around her, to free herself and her writing from traditional sexual limitations. Even more daringly, she responded to their language with her own feminized discourse, developing an innovative way of expressing her sexual and artistic expressions."--Publisher's description.